Analysis of Data Mining for Forecasting Total Goods Delivery with Moving Average Method - M. Azman Maricar; Putu Widiadnyana; I Wayan Arta Wijaya (International Journal of Engineering and Emerging Technology, 2017)
In the logistics and distribution of goods, the expedition service is necessary, because the expedition is an important part of a business that has a strong attachment to the distribution. The number of deliveries from an expedition per period is uncertain, sometimes the number increases or decreases. This may result in an imbalance between existing facilities and employees and the number of shipments from customers or company policies. To overcome this, required forecasting techniques that are able to predict total shipments, as well as predict which goods and products are the most widely sent. The moving average method using the last 5 period data is used as a way of forecasting. MAPE (Mean Absolute % Error) is used as a test method, and a result of 34 %, indicates that the method is feasible to use.